2010
DOI: 10.1104/pp.110.155077
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisRAP2.2: An Ethylene Response Transcription Factor That Is Important for Hypoxia Survival    

Abstract: Arabidopsis (Arabidopsis thaliana) RAP2.2 (At3g14230) is an APETALA2/ethylene response factor-type transcription factor that belongs to the same subfamily as the rice (Oryza sativa) submergence tolerance gene SUB1A. RAP2.2 is expressed at constitutively high levels in the roots and at lower levels in the shoots, where it is induced by darkness. Effector studies and analysis of ethylene signal transduction mutants indicate that RAP2.2 is induced in shoots by ethylene and functions in an ethylene-controlled sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
306
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 306 publications
(325 citation statements)
references
References 82 publications
(114 reference statements)
13
306
2
4
Order By: Relevance
“…AlaAT was induced under various oxygen stresses and that is probably why AlaAT was the only nitrogen metabolism gene described among the 49-core hypoxiaresponsive genes expressed in various tissues of 7-day old Arabidopsis plantlets grown on solid medium and gassed for 2 h by argon (99.99 %) (Mustroph et al 2009). AlaAT expression was similarly induced in Agrobacterium rhizogenes-induced hairy roots soaked in hypoxic (0.5 % O 2 ) liquid medium (Klok et al 2002), in young seedlings soaked in hypoxic (3 % O 2 ) (Liu et al 2005a) or anoxic (90 % N 2 -10 % H 2 ) (Loreti et al 2005) liquid medium and in plantlets grown on solid medium under anoxic (99.99 % argon), or hypoxic (1 or 1.5 % O 2 ) atmosphere (van Dongen et al 2009;Hinz et al 2010). Other nitrogen metabolism genes, without being ubiquitously overexpressed under low oxygen stress, were more or less up-regulated in specific studies, e.g., glutamate dehydrogenase (GDH2; At5g07440), glutamate decarboxylase (GDC1; At5g17330) and glutamate synthase (NADH-GOGAT; At5g53460).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…AlaAT was induced under various oxygen stresses and that is probably why AlaAT was the only nitrogen metabolism gene described among the 49-core hypoxiaresponsive genes expressed in various tissues of 7-day old Arabidopsis plantlets grown on solid medium and gassed for 2 h by argon (99.99 %) (Mustroph et al 2009). AlaAT expression was similarly induced in Agrobacterium rhizogenes-induced hairy roots soaked in hypoxic (0.5 % O 2 ) liquid medium (Klok et al 2002), in young seedlings soaked in hypoxic (3 % O 2 ) (Liu et al 2005a) or anoxic (90 % N 2 -10 % H 2 ) (Loreti et al 2005) liquid medium and in plantlets grown on solid medium under anoxic (99.99 % argon), or hypoxic (1 or 1.5 % O 2 ) atmosphere (van Dongen et al 2009;Hinz et al 2010). Other nitrogen metabolism genes, without being ubiquitously overexpressed under low oxygen stress, were more or less up-regulated in specific studies, e.g., glutamate dehydrogenase (GDH2; At5g07440), glutamate decarboxylase (GDC1; At5g17330) and glutamate synthase (NADH-GOGAT; At5g53460).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…It is important to note that the expression of these genes under aerobic condition was as high as that in wild type under anaerobic condition (Gibbs et al 2011). In Arabidopsis seedlings, overexpressing RAP2.2 (Hinz et al 2010) or its closest homolog RAP2.12 (Licausi et al 2011) anaerobic carbon metabolism genes were strongly induced during low oxygen stress; changes in gene expression were accompanied by improved survival of the seedlings to flooding-induced low oxygen stress. Microarray analysis followed by quantitative RT-PCR for the comparison of genes induction by hypoxia treatment in wild type and Arabidopsis silenced in both RAP2.2 and RAP2.12 showed a reduced induction of anaerobic carbon metabolism genes in miRNA lines and confirmed that these transcription factors are required for the regulation of hypoxia-induced genes (Licausi et al 2011;Hinz et al 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations